PEMBELAJARAN BERBASIS VIDEO UNTUK MENINGKATKAN TEKNIK DASAR SHOOTING MENGGUNAKAN PUNGGUNG KAKI DALAM PERMAINAN SEPAK BOLA - Ikhsan, Haerul (Jambura Arena of Physical Education and Sports, 2025)
This study aims to improve the basic shooting technique using the instep in soccer for ninth-grade students at SMA Negeri 1 Kota Gorontalo through video instruction. Shooting technique is a crucial element in soccer because it can determine the outcome of a match. However, many students have not yet mastered this technique. Using video as a learning tool is expected to provide a clearer understanding of this technique. The method used in this study was classroom action research (CAR), with 30 ninth-grade students as subjects. The results showed that video instruction improved students' understanding of the instep shooting technique. Before implementing the video instruction, only 40% of students were able to perform this technique correctly, whereas after the implementation, the percentage increased to 85%. These findings indicate that video instruction can be an effective alternative in Physical Education (PJOK) learning, particularly in teaching basic soccer techniques